An exploratory study on the use of camera phones and pico projectors in rural India - Mathur, Akhil; Ramachandran, Divya; Cutrell, Ed; Balakrishnan, Ravin (MobileHCI 2011: Proceedings of the 13th International Conference on Human Computer Interaction with Mobile Devices and Services, 2011)
We explore the potential of using camera phones and pico projectors in rapid creation and presentation of digital content in a development context. A camera phone based content authoring application was designed and deployed with three different user populations in the domains of classroom education and health care. Our findings show that despite the variations in education levels, cultural background, and technology exposure, users successfully created and presented different forms of digital content using the camera phone and pico projector.